# How would you solve for x when you have the problem: 2(x+1)=6(x-3).

*print*Print*list*Cite

### 2 Answers

We use Distributive property on both sides. a(b + c) = a*b + a*c.

`2*x + 2*1 = 6*x + 6*-3`

`2x + 2 = 6x - 18`

Put all the terms with "x" on left side, and all the other terms on right side.

Subtract both sides by 6x.

`2x - 6x + 2 = -18`

Combine like terms.

`-4x + 2 = -18`

Subtract both sides by 2.

`-4x = -20`

Divide both sides by -4.

`x = 5`

THerefore,** x = 5**.

2 ( x + 1 ) = 6 ( x - 3 )

To solve this equation , first distribute the 2 . By distributing the 2 , you should get

2x + 2 = 6 ( x - 3 ) now distribute the 6

By distributing the 6 , you should get

2x + 2 = 6x - 18 now subtract 6x on both sides , that way all the " x " variables are on the same side

By subtracting 6x on both sides , you should get

-4x + 2 = -18 now subtract 2 on both sides

By subtracting 2 on both sides , you should get

-4x = -20 now divide by -4 on both sides to get " x " alone .

By dividing by -4 on both sides , you should get

x = 5 which is your answer.